Discrimination of Oribotritia species by oil gland chemistry (Acari, Oribatida) - Raspotnig, Günther (Springer Netherlands, 2011)
The chemical composition of secretions from opisthonotal (oil) glands in four species of the oribatid mite genus Oribotritia (Mixonomata, Euphthiracaroidea, Oribotritiidae) was compared by means of gas chromatography—mass spectrometry. The secretions of all, O. banksi (from North America) and three Austrian oribotritiids (O. berlesei, O. hermanni, O. storkani), are shown to be based on certain unusual compounds, the iridoid monoterpenes chrysomelidial and epi-chrysomelidial and the diterpene β-springene. These components probably represent general chemical characteristics of oribotriid oil glands. Their relative abundance in the secretions along with further components (mainly saturated and unsaturated C(13)-, C(15)-, C(17)-hydrocarbons, and the tentatively identified octadecadienal) led to well-distinguishable, species-specific oil gland secretions profiles. In addition a reduced set of “Astigmata compounds” (sensu Sakata and Norton in Int J Acarol 27:281–291, 2001)—namely the two monoterpenes neral and geranial—could be detected in extracts of O. banksi nevertheless indicating the classification of euphthiracaroids within the (monophyletic) group of “Astigmata compounds-bearing”-Oribatida. These compounds are considered to be apomorphically reduced in all Austrian species. Our findings emphasize the potential of chemosystematics using oil gland secretion profiles in the discrimination of morphologically very similar, syntopically living or even cryptic oribatid species.